PENGARUH KUALITAS PELAYANAN, CITRA MEREK DAN KEPUASAN PELANGGAN TERHADAP LOYALITAS PELANGGAN LOGISTIK PADA PT. TIKI JALUR NUGRAHA EKAKURIR (JNE) DI KOTA GRESIK - RETNO AYU MULFI (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2018)
This study aims to examine the effect of Service Quality, Brand Image and Customer Satisfaction on Logistics Customer Loyalty at PT. Tiki Track Nugraha Ekakurir (JNE) in the City of Gresik. Then a literature review and the preparation of hypotheses were carried out, data were also obtained from questionnaires on 96 Gresik people who had used PT. Tiki Nugraha Ekakurir Line (JNE) using nonprobability sampling technique. Testing is done using multiple linear regression. The results of the analysis show that service quality significantly affects customer loyalty, brand image significantly influences customer loyalty and customer satisfaction significantly influences customer loyalty.